Effects of Calcium Lignosulfonate and Silicic Acid on Ammonium Nitrate Degradation - Ahmet Ozan Gezerman; Burcu Didem Çorbacıoglu (Journal of Chemistry)
Ammonium nitrate salts are the most commonly used nitrogenous fertilizers in industry. However, storage of ammonium nitrate is problematic, since its initial properties can decline because of environmental factors, leading to large economic losses. In this study, in order to prevent the caking and degradation of ammonium nitrate, an alternative composition with additional calcium lignosulfonate and silicic acid was studied. The resulting fertilizer was analyzed by screening analysis, ion chromatography, and electron microscopy methods.